The Politics of Regional Disadvantage: Regional Differences in Public Sector Employment - Colley, L.; Brown, Kerry (-, 2015)
The notion of regional disparity has received attention by government as entire regions may lag national average indictors of wellbeing and performance through lack of natural resources or access to human capital. Regional prosperity is affected by many different circumstances, including government activities and public service participation in regional labour markets. This research offers a new conceptualisation of space, place and scale in the public employment context. It examines public service jobs across regions in a particular jurisdiction and analyses how public employment compares to other jobs in each regional labour market. The research concludes that public services and public employment policies play an important role in the quantity and quality of regional job opportunities, and that public service restructuring that involves job cuts and outsourcing will affect this regional prosperity in unforeseen ways.